2013
DOI: 10.1186/1472-6947-13-14
|View full text |Cite
|
Sign up to set email alerts
|

Does googling for preconception care result in information consistent with international guidelines: a comparison of information found by Italian women of childbearing age and health professionals

Abstract: BackgroundPreconception counseling is effective in reducing the risk of adverse pregnancy outcomes. The Internet is commonly used by women and health professionals to search for health information. We compared the consistency of preconception information found on the Internet with the recommendations published by American Journal of Obstetrics and Gynecology (AJOG) simulating a web search by women of childbearing age and health professionals.MethodsWe reviewed websites resulting from a Google search performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 30 publications
0
42
0
Order By: Relevance
“…On the other hand, presence of reliable health-related information on the web has been previously investigated in different areas, such as influenza [31], vaccinations [32], dental care [33], type 2 diabetes [34], ophthalmic conditions [35] and preconception health [36]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, presence of reliable health-related information on the web has been previously investigated in different areas, such as influenza [31], vaccinations [32], dental care [33], type 2 diabetes [34], ophthalmic conditions [35] and preconception health [36]. …”
Section: Discussionmentioning
confidence: 99%
“…However, healthcare practitioners in maternity services are a group perfectly positioned to discuss preconception nutrition. Though a large proportion of women seek information related to nutrition on the internet, they consider clinicians as reliable sources of information and hence having conversations related to diet and lifestyle in the clinic can help overcome other barriers such as misinformation and poor‐quality nutritional information on the internet 34 …”
Section: Barriers and Opportunities For Engaging With Women In The Prmentioning
confidence: 99%
“…In a recent survey, we showed that web-engaged women planning a pregnancy search for information on Google using preconception-related and pregnancy-related keywords [12]. This population is probably characterized by a peculiar profile and by specific preconception risk factors.…”
Section: Introductionmentioning
confidence: 99%